Review of liver biopsies at Red Cross War Memorial Children's Hospital over a six-year period - Mokoto, Tshepang (Department of Paediatrics and Child Health, 2026)
Background: Liver biopsy is a fundamental diagnostic tool in clinical hepatology, also playing a crucial role in the prognostication and management of liver diseases. Previous studies at various centres have examined liver biopsies in the context of liver disease workups, including indications, histological findings and procedural complications. Objectives: To ascertain the role of liver biopsy in the evaluation of patients with liver diseases at Red Cross War Memorial Children's Hospital (RCWMCH) over a six-year period. Method: This retrospective descriptive study includes all paediatric patients who underwent liver biopsies at RCWMCH between 01/01/2018 and 30/06/2023. Results: Seventy-five patients were screened for eligibility; six were excluded due to missing data and files, subsequently the study comprised of sixty-nine participants. Most liver biopsies were performed percutaneously under ultrasound guidance (n=45, 65%). There were three (4.3%) major complications, and no minor complication. The tissue yield was 95.7% (n = 66), with histopathological findings guiding clinical management in 50 patients (72%). Most frequent diagnoses were biliary atresia and autoimmune hepatitis. The commonest indications for liver biopsy were hyperbilirubinemia and suspected graft rejection. Conclusion: Although liver biopsy is an invasive procedure, if guidelines are adhered to and performed by experienced staff it can be justified when using standard indications as it has a low complication rate in our setting and directly influence management in the majority of cases